PENGARUH PERAN IBU DALAM PEMELIHARAAN KESEHATAN GIGI DAN MULUT TERHADAP KEJADIAN KARIES GIGI PADA SISWA KELAS I SD NEGERI JUBELAN 02 KECAMATAN SUMOWONO - Endah Aryati Ekoningtyas; Umi Salamah Apriliana; Erni Mardiati (Jurnal Kesehatan Gigi, 2014)
ABSTRACT The role of mother in the maintenance of oral health includes the removal of plaque and debris on the teeth that can be done every day with a toothbrush, supervise child's diet, eliminating bad habits and check their child's teeth or facilities to health facilities is a factor that plays a role in preventing caries teeth in children. Dental caries is one form of tooth decay is most often experienced by children of school age. The incidence of dental caries in primary school students in the District of Sumowono Jubelan 02 is the average def-t 8.1 and DMF-T 1.6. The purpose of this study was to determine the role of the mother in the maintenance of oral health on the incidence of dental caries in first grade primary school students Jubelan 02 District of Sumowono 2014. This research is a descriptive cross sectional design research. The population in this study were for 24 student, all students in first class of Primary School of Jubelan 02 Sumowono, Semarang. Analisis is doing descriptively by cross tabulation. Measures used was a questionnaire. The results showed that all the mother's role in the maintenance of oral health is Most of the categories, but the incidence of caries included in the high category in the amount of 75%. The results showed that no influence of the mother's role in the maintenance of oral health on the incidence of caries incidence in children of primary school age.Key words :  Role Mommy, Maintenance Dental and Oral Health, Dental Caries Genesis